ABNORMAL BEHAVIOR DETECTION IN CROWD SCENES (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we suggest a unique method for unexpected human movement region injam-packed scenes/home. In particular, rather than figuring out or fragmenting humans, wecontrived a gifted approach, known as a motion impact map, for addressing human sportingactivities. The essential element of the proposed movement effect map is that it absolutelymirrors the movement characteristics of the development velocity, development bearing, andlength of the articles or subjects and their collaborations inner a part grouping.